Intralayer multi-material structure stainless-steel/nickel-superalloy fabricated via laser-powder bed fusion process. (January 2023) - Errico, Vito; Posa, Paolo; Fusco, Andrea; Angelastro, Andrea; Luisa Campanelli, Sabina
Abstract: This work aims to contribute to the progress in the fabrication of multi-material structures using the Laser-Powder Bed Fusion technology. To manufacture an intralayer multi-material sample, an ad-hoc partitioning system was developed for the powder chamber. The manufacturability of a Stainless-Steel/Nickel-superalloy multi-material component, having a strong bond at the interface, which appeared cracks- and porosity free, was demonstrated. To characterize the sample in-situ and real-time, an optical monitoring system was implemented. The latter can allow for detection, in real-time and in a layer-by-layer manner, of any malfunctions during the process and contaminations between the two different materials.